Enhancing Students' Learning Outcomes through the Implementation of the Team Games Tournament Model at SD Negeri 4 Banda Aceh - Raihan, Putri Ashfi Raihan; Aski, Nur; Tursinawati, Tursinawati (Lombok Institute, 2025)
Mathematics is often perceived by students as a complicated subject, leading to learning outcomes that are consistently lower compared to other subjects. To address this issue, this study implemented the cooperative learning model Team Games Tournament (TGT) as an intervention to improve mathematics learning outcomes. This classroom action research (CAR) was conducted with fourth-grade students (Class IVA) at SD Negeri 4 Banda Aceh during the 2024/2025 academic year. The study aimed to provide an objective description of the improvement in students' achievement in learning the area of rectangles and squares through the TGT model. The research was carried out in two cycles, each consisting of phases of planning, action, observation, and reflection. The findings indicate that applying the TGT model significantly improved students’ mathematics learning outcomes. This improvement is evidenced by the increase in the average score and the mastery learning rate from Cycle I to Cycle II. Mastery learning increased from 67% in Cycle I to 83% in Cycle II. These results suggest that the TGT model effectively enhances students’ understanding of geometric concepts, particularly in calculating the area of rectangles and squares.